Location and marking of cadastral boundaries in Nordic countries - Paasch, Jesper Mayntz; Paulsson, Jenny; Skovsgaard, Tanja; Mjøs, Leiv Bjarte; Halme, Pekka; Dyrkolbotn, Sjur (Nordic Journal of Surveying and Real Estate Research, 2023)
Cadastral boundaries are key components for ordering the ownership of real property by dividing it into territories. This study analyses the similarities and differences in marking cadastral boundaries in Denmark, Finland, Norway, and Sweden. A case study was conducted by examining legislations, ordinances, guidelines, and other instructions. These are issued by both the respective national governments, and associated agencies responsible for real property formation and demarcation of boundaries, such as, the national cadastral authorities. We describe, analyse, and discuss the visual division between properties, boundary marks, natural features used as real property boundaries, the information on boundaries in national registers, prescriptive rights, and the localization of boundaries in each country. The outcome of the study shows that there are many similarities between the four countries, but also differences. As an example, the materials used for demarcation differ between each country. Furthermore, the party performing the cadastral procedures range from governmental officials to licenced private surveyors. Finally, differences were noted in whether a real property boundary following a river or stream when created will change position if the river or stream changes course over time.